ASPP2 suppresses tumour growth and stemness characteristics in HCC by inhibiting Warburg effect via WNT/β‐catenin/HK2 axis. Issue 5 (8th February 2023) - Liang, Beibei; Jiang, Yuan; Song, Shaohua; Jing, Wei; Yang, Hao; Zhao, Li; Chen, Ya; Tang, Qiqi; Li, Xuhui; Zhang, Lisha; Bao, Haili; Huang, Gang; et al.
Abstract: Abnormal energy metabolism is one of the characteristics of tumours. In the last few years, more and more attention is being paid to the role and regulation of tumour aerobic glycolysis. Cancer cells display enhanced aerobic glycolysis, also known as the Warburg effect, whereby tumour cells absorb glucose to produce a large amount of lactic acid and energy under aerobic conditions to favour tumour proliferation and metastasis. In this study, we report that the haploinsufficient tumour suppressor ASPP2, can inhibit HCC growth and stemness characteristics by regulating the Warburg effect through the WNT/β‐catenin pathway. we performed glucose uptake, lactate production, pyruvate production, ECAR and OCR assays to verify ASPP2 can inhibit glycolysis in HCC cells. The expression of ASPP2 and HK2 was significantly inversely correlated in 80 HCC tissues. Our study reveals downregulation of ASPP2 can promote the aerobic glycolysis metabolism pathway, increasing HCC proliferation, glycolysis metabolism, stemness and drug resistance. This ASPP2‐induced inhibition of glycolysis metabolism depends on the WNT/β‐catenin pathway. ASPP2‐regulated Warburg effect is associated with tumour progression and provides prognostic value. and suggest that may be promising as a new therapeutic strategy in HCC.